Development of Pla Suture Materials by Extrusion, Electrospinning and Supercritical co2 Impregnation of Ibuprofen and Naproxen - Romero-Figueroa, J; Galvez-Manriquez, D; Torres-Mediano, A; Araya-Lopez, C; Villegas-Vallejos, C; Garrido-Ayala, L; Rivera-Fuentealba, P (Elsevier B.V., 2023)
Suture materials based on poly (lactic acid) (PLA) were developed by means of two different methods: extrusion and electrospinning, which were followed by a supercritical CO2 impregnation treatment. Both suture materials obtained by these techniques were impregnated with naproxen and ibuprofen using supercritical CO2 as impregnation medium. The impregnation assays were carried out at two different pressures (12 and 15 MPa), a temperature of 40 °C and, a depressurization rate of 1 MPa/min. Depending on the drugs incorporated into the suture materials, the concentrations varied from 5.60 to 26.73 wt%. The addition of both drugs and, the preparation process itself caused different changes in the structural and thermal properties of the final suture materials. Finally, tests to quantify the kinetic release of both drugs were carried out in vitro by using a Franz diffusion cell, obtaining the concentration profiles of delivered compounds as a function of the time. © 2023 Elsevier B.V.